Social Justice and Trauma-Informed Care in Schools - Carrie E. Lorig; Aleksandra Krupina; Kris Varjas (International Journal of School Social Work, 2022)
Current understandings of trauma and implementations of trauma-informed care (TIC; SAMSHA, 2014) in school environments can be limited because the conceptualization, assessment, and treatment of trauma tends to focus on specific, identified histories of abuse. This reflects the impact of the Adverse Childhood Experiences (ACEs) prevalence study among the adult American population (Felitti et al., 1998). However, addressing and preventing trauma in youth populations encourages recognition of the particular and disproportionate ways trauma affects marginalized groups, especially in schools. Some advocates for TIC view TIC as a crucial partner in social justice (Crosby et al., 2018; Rigard et al., 2015). Social justice is defined as the elimination of systemic oppression and institutional barriers with the goal of ensuring equitable access to opportunities and resources for all (Graybill et al., 2018). This article aims to consider the intersections of trauma-informed care and the aims of social justice so schools might recognize trauma as both individual and systemic and make their trauma-informed frameworks inclusive of diverse experiences. This article suggests what can be done through the use of the TIC framework created by SAMHSA (2014), which will benefit from being integrated from school- and evidence-based frameworks like MTSS.
Keywords: School Mental Health Professionals; Trauma; Trauma-Informed Care; Social Justice; Prevention; Universal